Winner’s Curse on Malaysian IPOs: Does the Phenomenon Still Exist? - Che Yahya, Norliza; Mohd Rashida, Rasidah; Le Thuy Ngoc, An; Anwar, Ayesha (The Indonesian Capital Market Review, 2025)
This study examines the winner’s curse phenomenon through Amihud and Yong’s winner’s curse measurements. Amihud’s allocation rate (ALLOCTJ) is the natural log of the reciprocal of investor demand or oversubscription ratio while Yong’s institutional investor participation is gauged based on a type of IPOs which is issued via private placement (DPRIVATE). Using data set from 560 initial public offerings (IPOs) issued from January 2000 until December 2022 for listing on Bursa Malaysia, the results of the cross-sectional multiple regression analyses show that ALLOCTJ and DPRIVATE are consistently significantly negative in influencing initial returns of the IPOs. The former relationship indicates that uninformed investors are more likely to win IPOs which are not demanded by the informed investors, and subsequently the IPOs produce low or negative initial returns. In the meantime, the latter relationship suggests that IPOs that are not offered to institutional investors are deliberately underpriced to allure all skeptical investors back into the new shares market.